The Phenomenology of Ma‘rifat al-Hallaj: Interpreting Anā al-Ḥaqq Amidst the Spiritual Crisis of the Contemporary Era: English - Moh. Sholeh Baharis; Abdul Kadir Riyadi (Tasfiyah: Jurnal Pemikiran Islam, 2026)
This article examines the phenomenology of al-Hallaj’s ma‘rifat through an interpretation of the phrase “Anā al-Ḥaqq” in the context of the contemporary spiritual crisis. The main research questions include: how al-Hallaj’s ma‘rifat is understood as a transformation of mystical consciousness, how “Anā al-Ḥaqq” is interpreted phenomenologically, and how this experience is relevant in addressing the spiritual crisis of modern humanity. This study employs a literature review method with a qualitative-philosophical approach, utilizing phenomenological analysis of consciousness and textual readings of al-Hallaj’s primary sources, particularly Kitāb al-Ṭawāsīn, supported by contemporary academic studies. The results of the study indicate that al-Hallaj’s ma‘rifat is a spiritual experience characterized by tazkiyah, fanā’, baqā’, and tajallī, thereby shifting the center of consciousness from the empirical ego toward Divine Presence. Within this framework, “Anā al-Ḥaqq” should not be understood as an ontological identity claim between humanity and God, but rather as a linguistic testimony to a consciousness that has transcended the subject–object duality. A phenomenological analysis reveals that the “Ana” in this expression is not al-Hallaj’s biographical self, but a subject that has undergone the dissolution of the ego and appears as an atsar (trace) of al-Haqq. This finding affirms that al-Hallaj’s Sufism is not only significant as a classical mystical legacy but also relevant as a spiritual paradigm capable of addressing the crisis of meaning, the formalization of religion, and the existential alienation of contemporary humanity. Thus, this article contributes to bridging classical Sufism, the phenomenology of religion, and the problems of modern spirituality through a more textual, philosophical, and contextual reading.